2016
DOI: 10.1007/s00259-016-3478-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of 18F-FDG PET before and after induction chemotherapy for the early prediction of a poor pathologic response to subsequent preoperative chemoradiotherapy in oesophageal adenocarcinoma

Abstract: PurposeThe purpose of our study was to determine the value of 18F-FDG PET before and after induction chemotherapy in patients with oesophageal adenocarcinoma for the early prediction of a poor pathologic response to subsequent preoperative chemoradiotherapy (CRT).MethodsIn 70 consecutive patients receiving a three-step treatment strategy of induction chemotherapy and preoperative chemoradiotherapy for oesophageal adenocarcinoma, 18F-FDG PET scans were performed before and after induction chemotherapy (before p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…It provided much-needed knowledge to help to make relevant individualized treatment decisions in the near future. The study of van Rossum et al (6) confirmed the results of previous studies which studied smaller patient cohorts (7)(8)(9), and also found a significant correlation between metabolic response and histopathologic response (7-11). The current study showed a higher predictive value, probably due to the use of a newer generation PET-scanner, with higher sensitivity and intrinsic resolution as compared to previous studies (7-9).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…It provided much-needed knowledge to help to make relevant individualized treatment decisions in the near future. The study of van Rossum et al (6) confirmed the results of previous studies which studied smaller patient cohorts (7)(8)(9), and also found a significant correlation between metabolic response and histopathologic response (7-11). The current study showed a higher predictive value, probably due to the use of a newer generation PET-scanner, with higher sensitivity and intrinsic resolution as compared to previous studies (7-9).…”
supporting
confidence: 81%
“…In the study of van Rossum et al (6) this imaging biomarker was FDG-PET, which significantly increased the predictive value of response to trimodality treatment. It provided much-needed knowledge to help to make relevant individualized treatment decisions in the near future.…”
mentioning
confidence: 99%
“…Studies have demonstrated the usefulness of 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/CT for early response evaluation and prognosis assessment (Carr et al 2010, Takahashi et al 2012, Nakajo et al 2017. Recently, except standardised uptake value (SUV), 18 F-FDG PET/CT parameters, such as metabolic tumour volume (MTV) and total lesion glycolysis (TLG), have been shown to be of much clinical relevance in solid tumours such as oesophageal and pancreatic adenocarcinoma (Sakane et al 2017, van Rossum et al 2017. However, little has been reported for DTC, particularly for RAIR-DTC, after TKI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognostic value of 18 F-FDG PET response after chemoradiotherapy has not been definitively established, most likely because of the confounding effects of radiationinduced esophagitis (9,10). On the other hand, 18 F-FDG PET response after induction chemotherapy seems to be a more dependable imaging marker for predicting survival (11)(12)(13). Previous studies have suggested that 18 F-FDG PET response after induction chemotherapy could predict pathologic complete response (pCR) and was associated with survival outcomes in esophageal cancer patients treated with induction chemotherapy followed by neoadjuvant or definitive chemoradiotherapy (11)(12)(13).…”
mentioning
confidence: 99%
“…On the other hand, 18 F-FDG PET response after induction chemotherapy seems to be a more dependable imaging marker for predicting survival (11)(12)(13). Previous studies have suggested that 18 F-FDG PET response after induction chemotherapy could predict pathologic complete response (pCR) and was associated with survival outcomes in esophageal cancer patients treated with induction chemotherapy followed by neoadjuvant or definitive chemoradiotherapy (11)(12)(13). Moreover, an early 18 F-FDG PET response could provide useful information for choosing a chemotherapy regimen to be used during radiation for those who do not show an 18 F-FDG PET response (14).…”
mentioning
confidence: 99%